Atributos físicos do solo e a produtividade de soja e milho em áreas sob tráfego controlado de máquinas agrícolas - Girardello, Vitor Cauduro (2014)
The Soil compaction has been induced in the no-tillage (NT), mainly due to machinery traffic conditions in soils with high humidity. This traffic is essential for crop management, impossible to put out of the field. Alternatively to try to solve this problem the concept of controlled traffic system (CTF) of machines, which is the containment and permanent separation of local traffic machine of free traffic. In most incipient case of disciplined traffic system of the machines is an initial alternative to full deployment. In this sense an experiment was conducted during two crop years in a commercial area, managed under the NT using techniques of AP in the Não Me Toque city, RS state. The soil is Red Latossol with Cfa climate following Koppen classification. The treatments were: a) No Traffic (ST) b) traffic Spray (TP) c) Traffic Tractor (TT) and d) Maximum Traffic (TM). The assessments were: bunk density, macroporosity, microporosity, total porosity in the soil layers: 00-0.05; 0.05 0.10; 0,10 0.20 e 0.20 -0.30 m , water infiltration, penetrometer resistence (PR), root systems and yeld in the corn and soybean. In Céu Azul city, PR state, have another experiment was also conducted to study the traffic discipline within the commercial fields,but only soyebean field and with similar treatments to those used in RS. The results obtained in Paraná was observed that treatments with control traffic farming had 8% less yeld. Changes in soil physical properties not change significantly after the traffic. In the two case investigated it was found that the controlled traffic has feasibility in implementation and improvement in soil physical properties and increased yeld of corn and soybeans in southern Brazil.